Perovskite solar cell and preparation method thereof
Patent Information
- Application Number
- CN202310496315.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-05-05
AI Technical Summary
导致其在光、氧、水、热等条件下运行稳定性较差
[0031]This invention first discloses a perovskite photoactive layer for solar cells. The perovskite layer is a perovskite layer containing DBSA additive, which is introduced into the perovskite precursor to form the perovskite layer. The carboxylic acid groups on the succinic acid molecular backbone and the introduced Br atoms passivate defects in the perovskite film while effectively regulating the crystallization process of the perovskite film, improving the crystallinity of the perovskite film, increasing the grain size, and reducing the nonradiative recombination loss of photogenerated carriers. This synergistic effect further improves the photoelectric conversion efficiency and stability of the perovskite solar cell.
Smart Images

Figure CN116437672B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology and its fabrication technology, and specifically to a perovskite solar cell and its fabrication method. Background Technology
[0002] Energy is a vital guarantee for human economic and technological development. With the rapid development of human society, energy consumption has increased rapidly. Traditional fossil fuels (such as coal, oil, and natural gas) are non-renewable energy sources, and their total reserves will continue to decrease with development and use, making it difficult to meet the needs of human society. On the other hand, the use of fossil fuels produces large amounts of greenhouse gases and soot, causing the greenhouse effect, which seriously damages the natural environment and has adverse effects on human health. Therefore, solar cells, with their advantages of high performance, low cost, and environmental friendliness, have gradually emerged. Thanks to the joint efforts of photovoltaic professionals worldwide, the photoelectric conversion efficiency of perovskite solar cells has been continuously improved, increasing from 3.8% to the latest certified 25.7% after more than a decade of development, demonstrating extremely attractive application prospects.
[0003] There are various commonly used light-absorbing materials for perovskite solar cells, such as CsPbX3, FAPbX3, MAPbX3, FAMAPbX3, CsFAMAPbX3, and RbCsFAMAPbX3, where X represents a halogen. However, regardless of the perovskite composition used as the light-absorbing layer, it faces challenges related to crystal quality and lattice defects. This results in poor operational stability under conditions of light, oxygen, water, and heat. Furthermore, since most perovskite thin films are prepared using solution methods, this means that numerous defects exist both internally and on the surface of the perovskite film. These defects not only affect the photoelectric conversion efficiency of the final device but also serve as active sites for film degradation and decomposition. Therefore, high-quality perovskite thin films are crucial for the performance of perovskite solar cells.
[0004] In summary, existing perovskite solar cells suffer from the aforementioned technical problems. Summary of the Invention
[0005] The purpose of this invention is to provide a perovskite solar cell by introducing a multifunctional additive molecule to effectively regulate the crystallization process and crystal quality of the perovskite thin film, and to provide a method for preparing a perovskite solar cell, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0006] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution:
[0007] A perovskite photoactive layer for solar cells, wherein the perovskite layer is a perovskite layer containing DBSA additive, and DBSA is introduced as an additive into the perovskite thin film precursor to form the perovskite layer.
[0008] Furthermore, the perovskite layer containing DBSA additive is prepared by: spin-coating a perovskite precursor solution containing DBSA onto the pretreated electron transport layer using a solution method, and then annealing and crystallizing it on a hot table after spin-coating to obtain a perovskite layer containing DBSA additive as the light-absorbing layer of the solar cell.
[0009] The DBSA content in the perovskite precursor solution was 0.001 mg / mL.
[0010] After spin coating, the coating is placed on a hot table at 110°C for annealing for 60 minutes.
[0011] Furthermore, the perovskite precursor solution is a 1.4M Rb solution. 0.03 Cs 0.05 FA 0.9 MA 0.05 PbI3, where FA is NH2CHNH2 + MA is CH3NH3 + The solvent is a mixture of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO);
[0012] The volume ratio of DMF to DMSO is 4:1;
[0013] In this process, after stirring and dissolving, the additive DBSA was added to obtain a perovskite precursor solution with an added concentration of 0.001 mg / mL, and the solution was stirred for 6 hours.
[0014] Furthermore, the perovskite precursor solution comprises: 645.4 mg lead iodide, 8.9 mg rubidium iodide, 11.8 mg cesium chloride, 11.1 mg methylamine iodine, 216.7 mg formamidinium iodine, 800 μL DMF, and 200 μL DMSO.
[0015] Another objective of this invention is to provide a perovskite solar cell, comprising a conductive substrate, an electron transport layer, an electron transport modification layer, a perovskite layer, a perovskite interface passivation layer, a hole transport layer, a hole transport modification layer, and a metal back electrode.
[0016] The electron transport layer is a tin oxide electron transport layer with a thickness of approximately 30-50 nanometers; the perovskite layer has a thickness of approximately 600-800 nanometers; the hole transport layer has a thickness of approximately 200-250 nanometers; the hole transport modification layer has a thickness of approximately 8-10 nanometers; and the metal back electrode has a thickness of approximately 100-120 nanometers.
[0017] The perovskite layer is the aforementioned perovskite layer containing DBSA additive.
[0018] Furthermore, the materials of the perovskite layer include, but are not limited to, CsPbX3, FAPbX3, MAPbX3, FAMAPbX3, CsFAMAPbX3, and RbCsFAMAPbX3.
[0019] Another object of the present invention is to provide a method for preparing a perovskite solar cell, comprising the following steps:
[0020] S1: A tin oxide electron transport layer is deposited on a clean FTO conductive glass using a chemical bath method. After deposition, the glass is annealed at 170°C for 1 hour to obtain a dense tin oxide electron transport layer.
[0021] S2: The above tin oxide electron transport layer was subjected to ultraviolet ozone treatment for 15 minutes, and then a 0.75 mg / mL KCl solution was spin-coated onto the above substrate and annealed at 100°C for 10 minutes to complete the preparation of the electron transport modification layer.
[0022] S3: Prepare a perovskite layer containing DBSA additive according to the above method;
[0023] S4: Spin-coat 20 μL of phenylethyl ammonium iodide solution dissolved in isopropanol with a concentration of 5 mg / mL onto the above perovskite layer to obtain a perovskite interface passivation layer.
[0024] S5: Spin-coat a hole transport layer onto the perovskite interface passivation layer described above.
[0025] S6: On the hole transport layer mentioned above, a MoO3 hole transport modification layer with a thickness of 10 nanometers is vacuum thermally deposited.
[0026] S7: On the hole transport modification layer mentioned above, a silver electrode with a thickness of 120 nanometers is vacuum thermally deposited to complete the fabrication of the perovskite solar cell.
[0027] Furthermore, the S4 perovskite interface passivation layer is spin-coated at a speed of 5000 rpm for 30 seconds.
[0028] Furthermore, the method for synthesizing the material of the hole transport layer in S5 is as follows:
[0029] First, a solution of 2,2,7,7-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9-spirodifluorenechlorobenzene with a concentration of 100 mg / mL was prepared. Then, an acetonitrile solution of lithium trifluoromethanesulfonylimide, an acetonitrile solution of tri(bis(trifluoromethanesulfonyl)imide)cobalt salt, and 4-tert-butylpyridine were added. The mixed solution was then spin-coated onto the above substrate to obtain a hole transport layer.
[0030] The beneficial effects of this invention are as follows:
[0031] This invention first discloses a perovskite photoactive layer for solar cells. The perovskite layer is a perovskite layer containing DBSA additive, which is introduced into the perovskite precursor to form the perovskite layer. The carboxylic acid groups on the succinic acid molecular backbone and the introduced Br atoms passivate defects in the perovskite film while effectively regulating the crystallization process of the perovskite film, improving the crystallinity of the perovskite film, increasing the grain size, and reducing the nonradiative recombination loss of photogenerated carriers. This synergistic effect further improves the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0032] This invention effectively passivates uncoordinated Pb inside perovskite films. 2+ The defects were eliminated, but the stability of the film was improved by bonding the perovskite crystals at the grain boundaries. The halogen Br in DBSA is covalently connected to the framework, which effectively controls the crystallization process of the perovskite film without changing the perovskite lattice structure, forming a high-quality film with large grain size. The synergistic effect of the two improves the light absorption performance, photogenerated carrier transport capability, photoelectric conversion efficiency and stability of the perovskite film.
[0033] Secondly, a perovskite solar cell containing the aforementioned perovskite layer is disclosed, along with a method for its fabrication. Compared to perovskite solar cells based on a perovskite photoactive layer without added DBSA, the open-circuit voltage, short-circuit current density, fill factor, and operational stability of the cell are significantly improved. This method is simple to operate, highly reproducible, and easy to fabricate, providing a new approach for developing high-efficiency and stable perovskite solar cells.
[0034] Under standard test conditions (AM1.5G illumination), the perovskite solar cells prepared by the method of this invention have significantly higher open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency than existing technologies.
[0035] The perovskite solar cells prepared by this invention have significantly better stability than perovskite solar cells prepared based on traditional precursor solutions.
[0036] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description
[0037] Figure 1 This is a schematic diagram of the structure of the perovskite solar cell described in an embodiment of the present invention.
[0038] Figure 2 This is a scanning electron microscope image of the perovskite photoactive layer without additives described in an embodiment of the present invention.
[0039] Figure 3This is a scanning electron microscope image of the perovskite photoactive layer containing DBSA additive described in an embodiment of the present invention.
[0040] Figure 4 This is a comparison chart of the JV curves of perovskite solar cells containing DBSA additive and those without additive, as described in the embodiments of the present invention.
[0041] Figure 5 These are steady-state fluorescence test images of the perovskite layers containing DBSA additive and those without additive, as described in embodiments of the present invention.
[0042] Figure 6 This invention provides a comparison of the operational stability of perovskite solar cells with and without DBSA additives under illumination, as described in the embodiments of the present invention.
[0043] Figure 7 This is a comparison of the dark-state stability of perovskite solar cells containing DBSA additive and those without additive, as described in the embodiments of the present invention. Detailed Implementation
[0044] To more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below with reference to the accompanying drawings.
[0045] In fabricating perovskite solar cells, besides the DBSA-containing perovskite layer preparation described in this invention, the cell assembly techniques are generally described in most perovskite solar cell designs. This invention employs a commonly used assembly technique, and a schematic diagram of the perovskite solar cell structure is attached. Figure 1 As shown.
[0046] The present invention will now be described in conjunction with specific embodiments:
[0047] Example
[0048] In this embodiment, the preparation process using the method described in this invention is as follows:
[0049] A tin oxide electron transport layer was deposited on FTO conductive glass using a chemical bath method. After deposition, the glass was cleaned with deionized water and anhydrous ethanol for 5 minutes each, and then annealed at 170°C for 1 hour to obtain a dense tin oxide electron transport layer. Then, the glass was treated with ultraviolet ozone for 15 minutes, and a 60 μL solution of potassium chloride with a concentration of 0.75 mg / mL was spin-coated at 3000 rpm for 30 seconds. The glass was then annealed at 100°C for 10 minutes and treated with ultraviolet ozone for 15 minutes.
[0050] A perovskite precursor solution containing 0.001 mg / mL DBSA (645.4 mg lead iodide, 8.9 mg rubidium iodide, 11.8 mg cesium chloride, 11.1 mg methylamine iodine, 216.7 mg formamidinium iodine, 800 μL DMF, 200 μL DMSO) was spin-coated onto the above-mentioned tin oxide electron transport layer after UV ozone treatment using an antisolvent method. After spin-coating, the solution was annealed on a hot table at 110 °C for 60 minutes.
[0051] Scanning electron microscope images of the obtained perovskite layer are attached. Figure 3 As shown, the steady-state fluorescence of the obtained perovskite layer is as follows: Figure 5 As shown. Then, a perovskite interface passivation layer (5 mg / mL phenylethyl ammonium iodide isopropanol solution) was spin-coated at 5000 rpm for 30 seconds. Subsequently, a hole transport layer solution was spin-coated at 3800 rpm for 30 seconds. The hole transport layer solution was a mixture of 100 mg of 2,2,7,7-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9-spirodifluorene (Spiro-OMeTAD), 40.5 μL of 4-tert-butylpyridine (tBP), 24.5 μL of lithium trifluoromethanesulfonylimide (Li-TFSI) in acetonitrile (520 mg / mL), and 49 μL of tris(bis(trifluoromethanesulfonyl)imide) cobalt salt in acetonitrile (300 mg / mL) dissolved in 1 mL of chlorobenzene. Then, a 10-nanometer-thick molybdenum oxide hole transport modification layer is deposited by vacuum thermal evaporation, and finally, a 120-nanometer-thick silver electrode is deposited by vacuum thermal evaporation.
[0052] In this embodiment, a comparative example is designed to be used to compare with the present invention:
[0053] Comparative Example
[0054] A DBSA-free perovskite precursor solution was spin-coated during the preparation of the perovskite layer. Scanning electron microscope images of the resulting perovskite films are attached. Figure 2 As shown, the steady-state fluorescence of the obtained perovskite layer is as follows: Figure 5 As shown. Other preparation process parameters are the same as in the above embodiments.
[0055] Appendix Figure 5 The fluorescence results of the perovskite thin films obtained by spin-coating on quartz glass in the above embodiments and comparative examples show that the addition of the additive DBSA significantly inhibits non-radiative recombination related to defects in the film and improves the film quality.
[0056] Under standard test conditions (AM1.5G illumination), the open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of the perovskite solar cells prepared in the embodiments and comparative examples of this invention are detailed in the table below:
[0057]
[0058] Its current-voltage curve is shown in the attached figure. Figure 4 As shown in the figure, the open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of the perovskite solar cell prepared by the method of the present invention are significantly higher than those of the comparative perovskite solar cell without DBSA.
[0059] The batteries used in the examples and comparative cases were not encapsulated and were placed at room temperature under standard sunlight intensity for continuous maximum power output. The change in maximum power over storage time was tested. The test results are attached. Figure 6 As shown, the battery in the embodiment is more stable; after 700 hours of continuous output, the embodiment still retains 90% of its initial efficiency, while the comparative example only retains 62% of its initial efficiency.
[0060] The batteries used in the examples and comparative cases were unpackaged and placed in a nitrogen-filled glove box at room temperature. The device efficiency was tested as a function of storage time, and the test results are attached. Figure 7 As shown, the battery in the embodiment is significantly more stable, retaining 91% of its initial efficiency after 100 days of storage, while the comparative example only retains 79% of its initial efficiency.
[0061] It is evident that the perovskite solar cells prepared using this invention exhibit significantly better stability than those prepared using traditional precursor solutions. Compared to perovskite solar cells based on a perovskite photoactive layer without added DBSA, the open-circuit voltage, short-circuit current density, fill factor, and operational stability of the cells are significantly improved. This method is simple to operate, highly reproducible, and easy to prepare, providing a novel approach for developing high-efficiency and stable perovskite solar cells.
[0062] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Many modifications and variations can be made based on the content of this specification. These embodiments have been selected and specifically described in this specification to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A perovskite photoactive layer for solar cells, characterized in that: The perovskite photoactive layer is a perovskite layer containing 2,3-dibromosuccinic acid as an additive, which is formed by introducing 2,3-dibromosuccinic acid as an additive into the perovskite film precursor. The method for preparing the perovskite layer containing 2,3-dibromosuccinic acid additive is as follows: a perovskite precursor solution containing 2,3-dibromosuccinic acid is spin-coated onto the pretreated electron transport layer using a solution method. After spin-coating, the perovskite layer is placed on a hot table for annealing and crystallization to obtain the perovskite layer containing 2,3-dibromosuccinic acid additive as the light-absorbing layer of the solar cell. The perovskite precursor solution contained 0.001 mg / mL of 2,3-dibromosuccinic acid. After spin coating, the coating is placed on a hot table at 110°C for annealing for 60 minutes.
2. The perovskite photoactive layer for solar cells as described in claim 1, characterized in that: The perovskite precursor solution is a 1.4 M Rb solution. 0.03 Cs 0.05 FA 0.9 MA 0.05 PbI3, where FA is NH2CHNH2 + MA is CH3NH3 + The solvent is a mixture of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); The volume ratio of DMF to DMSO is 4:1; In this process, after stirring and dissolving, 2,3-dibromosuccinic acid was added to obtain a perovskite precursor solution with an added concentration of 0.001 mg / mL, and the solution was stirred for 6 hours.
3. The perovskite photoactive layer for solar cells as described in claim 2, characterized in that: The perovskite precursor solution comprises: 645.4 mg lead iodide, 8.9 mg rubidium iodide, 11.8 mg cesium chloride, 11.1 mg methylamine iodine, 216.7 mg formamidinium iodine, 800 μL DMF, and 200 μL DMSO.
4. The use of the perovskite photoactive layer for solar cells as described in any one of claims 1-3 as a solar energy absorbing layer product.
5. A perovskite solar cell, comprising a conductive substrate, an electron transport layer, an electron transport modification layer, a perovskite layer, a perovskite interface passivation layer, a hole transport layer, a hole transport modification layer, and a metal back electrode, characterized in that: in, The electron transport layer is a tin oxide electron transport layer with a thickness of 30-50 nanometers; the perovskite layer has a thickness of 600-800 nanometers; the hole transport layer has a thickness of 200-250 nanometers; the hole transport modification layer has a thickness of 8-10 nanometers; and the metal back electrode has a thickness of 100-120 nanometers. The perovskite layer is the perovskite photoactive layer as described in claim 1.
6. A method for fabricating a perovskite solar cell, characterized in that, Includes the following steps: S1: A tin oxide electron transport layer is deposited on a clean FTO conductive glass using a chemical bath method. After deposition, the glass is annealed at 170°C for 1 hour to obtain a dense tin oxide electron transport layer. S2: The tin oxide electron transport layer is subjected to ultraviolet ozone treatment for 15 minutes, and then a 0.75 mg / mL KCl solution is spin-coated onto the tin oxide electron transport layer. The electron transport modification layer is then annealed at 100°C for 10 minutes to complete the preparation of the electron transport modification layer. S3: A perovskite precursor solution containing 2,3-dibromosuccinic acid was spin-coated onto an electron transport modification layer using a solution method. After spin-coating, the layer was annealed and crystallized on a hot stage to obtain a perovskite layer containing 2,3-dibromosuccinic acid as the light-absorbing layer of a solar cell. The content of 2,3-dibromosuccinic acid in the perovskite precursor solution was 0.001 mg / mL. After spin-coating, the layer was annealed on a hot stage at 110°C for 60 minutes to prepare the perovskite layer containing 2,3-dibromosuccinic acid. S4: Spin-coat 20 μL of phenylethyl ammonium iodide solution dissolved in isopropanol with a concentration of 5 mg / mL onto the perovskite layer to obtain a perovskite interface passivation layer. S5: Spin-coat a hole transport layer onto the perovskite interface passivation layer; S6: A MoO3 hole transport modification layer with a thickness of 10 nanometers is vacuum thermally deposited on the hole transport layer. S7: A silver electrode with a thickness of 120 nanometers is vacuum thermally deposited on the hole transport modification layer to complete the fabrication of the perovskite solar cell.
7. The method for preparing a perovskite solar cell as described in claim 6, characterized in that: In step S4, the spin coating speed is 5000 rpm and the spin coating time is 30 seconds.
8. The method for preparing a perovskite solar cell as described in claim 6, characterized in that: The material synthesis method for the hole transport layer in S5 is as follows: First, a chlorobenzene solution of 2,2,7,7-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9-spirodifluorene with a concentration of 100 mg / mL was prepared. Then, an acetonitrile solution of lithium trifluoromethanesulfonylimide, an acetonitrile solution of tris(bis(trifluoromethanesulfonyl)imide)cobalt salt, and 4-tert-butylpyridine were added. The mixed solution was then spin-coated onto a perovskite interface passivation layer to obtain a hole transport layer.